2022
DOI: 10.1111/anae.15601
|View full text |Cite
|
Sign up to set email alerts
|

Implications of nocebo in anaesthesia care

Abstract: Nocebo refers to non-pharmacological adverse effects of an intervention. Well-intended procedural warnings frequently function as a nocebo. Both nocebo and placebo are integral to the generation of 'real' treatment effects and their associated 'real' side-effects. They are induced or exacerbated by: context; negative expectancy; and negative conditioning surrounding treatment. Since the late 1990s, the neuroscience literature has repeatedly demonstrated that the nocebo effect is mediated by discrete neurobiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 74 publications
(142 reference statements)
0
16
0
Order By: Relevance
“…Finally, pain risk communication may have significant nocebo effects (ie, where unintended negative suggestions/phrasing about a treatment/procedure result in increased adverse events) [ 39 ], such as loss of appetite, nausea, itching, and stomach pain [ 40 ]. Phraseology is important [ 39 ], and framing an opportunity to improve future patient comfort by identifying relevant and modifiable risk factors, instead of highlighting risks of pain and unmodifiable risk factors, might reduce these potential nocebo effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, pain risk communication may have significant nocebo effects (ie, where unintended negative suggestions/phrasing about a treatment/procedure result in increased adverse events) [ 39 ], such as loss of appetite, nausea, itching, and stomach pain [ 40 ]. Phraseology is important [ 39 ], and framing an opportunity to improve future patient comfort by identifying relevant and modifiable risk factors, instead of highlighting risks of pain and unmodifiable risk factors, might reduce these potential nocebo effects.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, pain risk communication may have significant nocebo effects (ie, where unintended negative suggestions/phrasing about a treatment/procedure result in increased adverse events) [ 39 ], such as loss of appetite, nausea, itching, and stomach pain [ 40 ]. Phraseology is important [ 39 ], and framing an opportunity to improve future patient comfort by identifying relevant and modifiable risk factors, instead of highlighting risks of pain and unmodifiable risk factors, might reduce these potential nocebo effects. As 1 of the design requirements of our prototype is to present risk in a nonthreatening manner, we may wish to limit the use of the initial prototype to clinicians, while developing a version that focuses on “optimizing comfort” rather than “reducing pain” for sharing with family members.…”
Section: Discussionmentioning
confidence: 99%
“…While providing honest and accurate information is important, studies have shown how the impact of the words may be mitigated or altered in the way they are presented [17] and how possible therapeutic reframing [16, 18] may help. Arrow et al.…”
Section: Discussionmentioning
confidence: 99%
“…There were statements with evidence of nocebo communication for example `you will need strong painkillers´may suggest that `strong pain´will inevitably occur postoperatively. Such phrases increase negative expectancy and evidence suggests [16] are associated with the pain experience [4,8,17]. A minority of leaflets had sentences which focused on comfort, healing, benefit of surgery and the role of the medical staff to assist the patient in their recovery.…”
Section: This Suggests That Patient Information Leaflets Across Nhsmentioning
confidence: 99%
“…
We read with interest the article by Arrow et al [1]. It raises a number of interesting points related to the impact of language used by anaesthetists and the potentially negative impact this may have on the patient's experience and perception of their care.
…”
mentioning
confidence: 99%